Factores determinantes de la rentabilidad de las instituciones microfinancieras del Perú - Lizarzaburu Bolaños, Edmundo R. (2020)
The objective is determine the factors that influence in the profitability of microfinance institutions in Peru. This study constitutes a first approximation to understand the factors that influence in the profitability of microfinance institutions in Peru. We were used the panel data model. Credit risk, operating efficiency, and market concentration were found to be negatively related to ROA, while capital efficiency was positively related to ROA.